Sailing Into Uncertainty - Business Model Evaluation for Wind-Assisted Ship Propulsion - Sadarangani,Victor; Fredriksson,Viktor (2026)
This thesis identifies and evaluates business model alternatives for Oceanbird’s Wing 560 rigid sail, a wind-assisted ship propulsion technology approaching broader commercialisation. The shipping industry’s complex ownership structures create split-incentive problems that complicate investment in fuel-saving technologies, making the choice of business model a strategic decision. Furthermore, the potential customers operate in an uncertain investment environment, where the product itself introduces even more uncertainties. Four business model alternatives: CAPEX, Leasing, Guaranteed savings, and Shared savings, are identified, partly through a literature review of energy efficiency contracting in the housing sector, and evaluated using Monte Carlo simulation. The model captures uncertainty in fuel prices, product performance, CO2 legislation, and critical failure events, producing distributions of the net present value of the investment, for all stakeholders. The results show that no single business model is universally optimal. On the Voyage charter market, CAPEX is the best-performing model. On the Time and Bareboat charter markets, the identified EPC-based models consistently outperform CAPEX and Leasing by resolving the split-incentive problem, with Guaranteed savings performing better than Shared savings. the weighted average cost of capital and product performance are identified as the most impactful parameters on overall viability, where conclusions are especially sensitive to changes in weighted average cost of capital. The overall robustness is however, deemed sufficient for the scope of the thesis. The best performing business model is not entirely explained by the results of the Monte Carlo simulation model. It is also a strategic decision shaped by Oceanbird’s strategy: their willingness to undertake the engineering development required to address green water limitations on the Voyage charter market, and their capacity to develop the performance monitoring infrastructure necessary to implement EPC-based models such as Guaranteed savings. Furthermore, the discussion also highlights the model’s limitations and exposure to epistemic risk, which provide grounds for future research.
Keywords: Business models; Wind Assisted Ship Propulsion; WASP; Monte Carlo Simulation; energy performance contracting; EPC; Shipping industry